ASSESSMENT OF THE QUALITY OF LIFE OF PATIENTS WITH TYPE 2 DIABETES COMPLICATED BY DIABETIC PERIPHERAL POLYNEUROPATHY ON THE BACKGROUND OF REDUCED CONTENT VITAMIN D3 IN THE BLOOD - Martynyuk, L. P.; Makarchuk, N. R.; Parkhomenko, L. F.; Sydorenko, O. L. (Nursing, 2024)
Introduction. Today, diabetes has reached the scale of a serious epidemic, which is growing rapidly. In 2021, the total number of people with diabetes was 537 million, and by 2045, more than 783 million are expected. This disease is often accompanied by diabetic peripheral polyneuropathy, in particular, in 70 % of people, 15 % of them have neuropathic pain, which significantly affects the quality of life. Studies also show a link between vitamin D3 deficiency and the risk of developing diabetes and diabetic peripheral neuropathy. The aim of the study – to assess the quality of life of patients with type 2 diabetes complicated by diabetic peripheral polyneuropathy against the background of reduced vitamin D3 content in the blood. The main part. The EuroQol-5D-5L questionnaire was used to assess the quality of life of 66 type 2 diabetes patients with existing neuropathic pain depending on the level of 25(OH)D in the blood. It was established that in these patients the deficiency of vitamin D3 prevailed over its insufficiency. According to the results of the survey, patients demonstrated moderate problems with walking, minor or moderate problems with independent washing and dressing, moderate difficulties in performing normal daily tasks, more than half of the surveyed patients were concerned about the presence of severe pain or discomfort, and moderate - almost all patients who remained, while the majority of patients noted slight or moderate anxiety or depression. Conclusions. Survey results for patients with diabetes mellitus and diabetic peripheral neuropathy indicate moderate problems with walking, minor or moderate problems with independent bathing and dressing, and moderate difficulties with normal activities of daily living. Patients experience mild to moderate anxiety or depression and significant to moderate discomfort. Vitamin D3 deficiency was found in patients, which requires control of its level for adequate correction with the help of non-drug and drug measures.